A methylenedianiline-based compound polyamide thin layer composite film and a preparation method thereof

CN122912705APending Publication Date: 2026-10-16CANGZHOU INSTITUTE OF TIANGONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611384122.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的目的是提供一种甲基联苯胺基化合物聚酰胺薄层复合膜的制备方法,以解决上述聚酰胺薄层纳滤膜稳定性差、渗透选择性上限平衡低的问题

Benefits of technology

本发明所选用的界面聚合制膜方式简单,实验条件温和,制膜过程相对较短。甲基联苯胺基化合物的高位阻、刚性可扭转特性使得其在与酰氯单体形成了高度交联的网络结构,6,6’-位甲基的高位阻阻止联苯的两个苯环在同一平面内,降低聚合物链的致密有效堆积,显著提升生成的聚合物薄膜的自由体积和孔隙率,进而有利于提升所制备的膜的渗透性。同时这种高度交联的网络结构使得该膜保持良好的分子截留能力,同时具有较好耐压性,热稳定性和长期稳定性。甲基联苯胺基化合物刚柔并济的特性使得制备的复合膜相较于传统的聚酰胺膜大大提高了聚酰胺膜的溶剂渗透性,同时对于小分子染料保持了较高的截留。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912705A_ABST
    Figure CN122912705A_ABST
Patent Text Reader

Abstract

The application discloses a kind of methyldiphenylamine-based compound polyamide thin layer composite membrane and preparation method thereof, belong to separation membrane technical field.The application is with polyacrylonitrile or polyimide ultrafiltration membrane as base film, after removing surface pore-forming agent, first soak in methyldiphenylamine-based compound alcohol solution, then soak in organic solution containing polyacyl chloride and carry out interfacial polymerization reaction, then through heat crosslinking, after soaking in organic solvent, post-processing is obtained Composite nanofiltration membrane.The application is based on the torsional characteristics of biphenyl skeleton, introduce the methyl group with large steric hindrance in 6,6 '-position, so that methyldiphenylamine-based compound has greater torsion angle, maintains non-planar torsion structure, so that the prepared composite membrane is significantly improved compared with planar monomer m-phenylenediamine and more free methyldiphenylamine-based polyamide membrane solvent flux, and the selectivity of organic small molecule dye does not obviously reduce, so it has higher application value in industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membrane separation technology, and in particular to a methylbenzidine-based polyamide thin-layer composite membrane and its preparation method. Background Technology

[0002] Separation and purification are crucial in industries such as pharmaceuticals, petrochemicals, and chemical manufacturing. Traditional thermal methods (including distillation and evaporation) are energy-intensive and can cause degradation of heat-sensitive compounds. As a promising alternative, membrane separation technology offers a highly efficient and energy-saving solution for the separation and concentration of low molecular weight substances at room temperature. The increasing reliance on polyamide thin films has made organic solvent nanofiltration (OSN) an indispensable technological advancement. OSN membranes typically have a molecular weight cutoff (MWCO) of 200–1000 Da, demonstrating significant scientific and practical value in catalyst recovery, active pharmaceutical ingredient separation, and solvent recovery. However, a common problem with these membrane materials is the balance between permeability and selectivity, as well as operational stability, which limits their application in industrial development. Therefore, the development of high-performance OSN membranes is crucial for the further expansion and application of membrane separation technology.

[0003] To further improve membrane permeability, two main approaches are employed. One approach is to reduce the thickness of the separation layer to decrease transport resistance. For example, Karan et al. (Science, 2015, 348(6241): 760-767) introduced a sacrificial layer of chromium hydroxide nanowires to regulate the diffusion of aqueous monomers, thereby adjusting the morphology of the separation layer and preparing an ultrathin separation layer with a thickness of approximately 10 nm. The other approach primarily involves controlling the microporous structure of the membrane to enhance its porosity and interpore connectivity. For instance, Maria F. Jimenez-Solomon et al. (Nature Materials, 2016, 15: 760-7.) used twisted phenols as aqueous monomers for interfacial polymerization, achieving enhanced microporosity and higher interconnectivity within the separation layer, resulting in a solvent permeability improvement of two orders of magnitude compared to membranes prepared using non-twisted planar monomers.

[0004] Currently, the development and application of commercially available polyamide thin-layer membranes for OSN applications has stagnated due to their low performance and limited solvent resistance. There is an urgent need to find polyamide thin-layer nanofiltration membrane materials with a higher cost-performance ratio. To address these problems, a solution is proposed below. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing a methylbenzidine-based polyamide thin-layer composite membrane, in order to solve the problems of poor stability and low upper limit of permeation selectivity of the above-mentioned polyamide thin-layer nanofiltration membrane.

[0006] To achieve the above-mentioned objectives, this invention provides a method for preparing a methylbenzidine-based polyamide thin-film composite film, comprising the following steps: (1) Immerse the base membrane in deionized water for 6 h to fully remove the pore-retaining agent on the membrane surface. The base membrane is a polyacrylonitrile or polyimide ultrafiltration membrane. (2) Remove the soaked base film and drain the surface water. Then soak it in a methylbenzidine compound alcohol-water mixed solution at 25°C for 1-10 min. After soaking, remove the base film and remove the water droplets remaining on the surface of the base film for later use. (3) At 25°C, the base membrane treated in step (2) is immersed in an organic solution for 1-10 min and then removed and the organic phase solution on the surface of the membrane is removed with an organic solvent, wherein the organic phase solution contains polyacrylamide chloride; (4) Place the composite nanofiltration membrane after the reaction in step (3) in an oven at 40-70℃ and heat for 1-10 min to perform thermal crosslinking; (5) Soak the composite nanofiltration membrane obtained in step (4) in an organic solution for 1 h-20 h to obtain a methylbenzidine-based polyamide thin-layer composite membrane.

[0007] Preferably, the structure of the methylbenzidine compound in the aqueous solution of the methylbenzidine compound of the present invention is as follows: .

[0008] Preferably, the solvent for the aqueous solution of the methylbenzidine compound in step (2) is a mixture of alcohol and water, and the alcohol is at least one of ethanol, methanol, and isopropanol.

[0009] More preferably, the proportion of alcohol in the solvent of the aqueous solution of the methylbenzidine compound in step (2) is 0.1%-100 wt.%.

[0010] Preferably, the polyacryl chloride is one or a mixture of several of pyromellitic chloride, isophthaloyl chloride, and terephthaloyl chloride; the concentration of the polyacryl chloride is 0.1 wt%-0.3 wt%.

[0011] Preferably, the organic solution in step (3) is prepared by dissolving polyacrylamide chloride in a polyamide thin layer, and the organic solution is at least one of n-hexane, isoalkanes or cyclohexane.

[0012] Preferably, the organic solvent in step (5) is used to treat the newly formed polyamide thin-layer composite nanofiltration membrane by soaking, and the organic solvent is at least one of acetone, tetrahydrofuran or ethanol.

[0013] The present invention has the following beneficial effects: The interfacial polymerization membrane-forming method selected in this invention is simple, the experimental conditions are mild, and the membrane-forming process is relatively short. The high steric hindrance and rigid torsion properties of the methylbenzidine compound enable it to form a highly cross-linked network structure with the acyl chloride monomer. The high steric hindrance of the 6,6'-methyl group prevents the two benzene rings of biphenyl from being in the same plane, reducing the dense and effective packing of the polymer chains, significantly increasing the free volume and porosity of the resulting polymer film, thereby improving the permeability of the prepared membrane. Simultaneously, this highly cross-linked network structure allows the membrane to maintain good molecular retention capacity, while also exhibiting good pressure resistance, thermal stability, and long-term stability. The combination of rigidity and flexibility of the methylbenzidine compound results in a composite membrane that significantly improves the solvent permeability of polyamide membranes compared to traditional polyamide membranes, while maintaining a high retention rate for small molecule dyes.

[0014] The composite nanofiltration membrane prepared by this invention has a high permeation flux (>25 LMH / bar) to organic solvents such as acetone and methanol, and can effectively retain dye molecules such as Orange G, Acid Fuchs Red, Acid Red 27, and Methylene Blue. It can be fully applied to chemical processes such as active drug separation, crude oil extraction, and catalyst recovery in organic solvent systems. Attached Figure Description

[0015] Figure 1 These are electron microscope images of the surface of the composite nanofiltration membrane prepared in Example 1 of this invention; Figure 2 This is a graph showing the separation performance of the composite nanofiltration membrane prepared in Example 1 of this invention for various dyes; Figure 3 This is a graph showing the permeation performance of the composite nanofiltration membrane prepared in Example 1 of this invention to various solvents; Figure 4 This is a graph showing the separation performance of the composite nanofiltration membrane prepared in Example 1 of this invention under different pressures; Figure 5 This is an electron microscope image of the surface of the composite nanofiltration membrane prepared in Comparative Example 2 of this invention; Figure 6 This is a graph showing the separation performance of the composite nanofiltration membrane prepared in Comparative Example 2 of this invention for various dyes; Figure 7 This is a graph showing the permeation performance of the composite nanofiltration membrane prepared in Comparative Example 2 of this invention to various solvents. Detailed Implementation

[0016] The technical solution of the present invention will be further defined below with reference to specific embodiments, but the scope of protection is not limited to the description.

[0017] In the following examples, the separation performance test conditions used were as follows: after pre-pressurizing for 2 hours at 0.6 MPa and 25°C, the pressure was adjusted to 0.5 MPa. The rejection rate of the prepared composite nanofiltration membrane to 50 ppm dye methanol solution and the permeation flux of various solvents were tested. The flux unit is LMH / bar (liters / square meter / hour / bar).

[0018] Example 1 A method for preparing a methylbenzidine-based polyamide thin-film composite film, comprising the following steps: (1) Soak the polyacrylonitrile ultrafiltration membrane in pure water for 4 h to remove the pore-retaining agent on the membrane surface; (2) Take out the above polyacrylonitrile ultrafiltration membrane, wipe the water droplets remaining on the surface of the ultrafiltration membrane with lint-free paper, and soak it in an ethanol aqueous solution with a methylbenzidine concentration of 0.1 wt% (ethanol ratio of 30 wt.%) for 5 min at 25°C. Take out the ultrafiltration membrane and remove the water droplets remaining on the membrane surface with a rubber roller for later use. (3) At 25°C, the polyacrylonitrile ultrafiltration membrane treated in step (2) was immersed in a hexane solution with a pyromellitic chloride concentration of 0.2 wt% and reacted for 10 min. (4) Place the composite nanofiltration membrane after the reaction in step (3) in an oven at 60 °C and heat for 8 min.

[0019] (5) The composite nanofiltration membrane obtained in step (4) was immersed in acetone for 12 h to obtain a methylbenzidine polyamide thin-layer composite nanofiltration membrane, the surface morphology of which is as follows: Figure 1 .

[0020] The prepared composite nanofiltration membrane was used to separate 4-p-nitroaniline (AR), Sudan Orange G (SOG), methyl orange (MO), orange yellow G (OG), acid fuchsin (AF), acid red 27 (AR27), and methylene blue (MB). The experimental results are as follows: Figure 2 As shown, the retention capacity gradually increases with the increase of dye molecular weight; the molecular weight cutoff of the above-mentioned polyamide thin-layer nanofiltration membrane is approximately 343 Da.

[0021] The prepared composite nanofiltration membrane was tested for permeation performance with various solvents, and the results are as follows: Figure 3 As shown, the composite nanofiltration membrane of this invention has a methanol permeability coefficient of 26.3 LMH / bar and an acetone permeability coefficient of 46.5 LMH / bar. Furthermore, the permeability of the composite nanofiltration membrane to various solvents exhibits a certain linear relationship with the binding parameters of the corresponding solvents.

[0022] The prepared composite nanofiltration membrane was subjected to three pressure cycles of 2-8 bar, and the changes in its separation performance were tested, as shown in the attached figure. Figure 4As shown, during these three cycles, the permeability coefficient of the composite nanofiltration membrane exhibits a linear relationship with the pressure, while the retention rate of Orange G remains above 97%, demonstrating excellent operational stability.

[0023] Example 2 A method for preparing a methylbenzidine-based polyamide thin-layer composite nanofiltration membrane, comprising the following steps: (1) Soak the polyacrylonitrile ultrafiltration membrane in pure water for 4 h to remove the pore-retaining agent on the membrane surface; (2) Take out the above polyacrylonitrile ultrafiltration membrane, wipe the water droplets remaining on the surface of the ultrafiltration membrane with lint-free paper, and soak it in an ethanol aqueous solution with a methyl benzidine concentration of 0.1 wt% (ethanol ratio of 30 wt.%) for 5 min at 25°C. Take out the ultrafiltration membrane and remove the water droplets remaining on the membrane surface with a rubber roller for later use. (3) At 25°C, the polyacrylonitrile ultrafiltration membrane treated in step (2) was immersed in a hexane solution with a pyromellitic chloride concentration of 0.2 wt% and reacted for 3 min. (4) Place the filter membrane after the reaction in step (3) in an oven at 60 °C and heat for 8 min.

[0024] (5) The composite nanofiltration membrane obtained in step (4) is immersed in acetone for 12 h to obtain a methylbenzidine polyamide thin-layer composite nanofiltration membrane.

[0025] The separation performance test of the prepared composite nanofiltration membrane showed that the methanol flux was 35.2 LMH / bar and the rejection rate of Orange G (MW 452 Da) was 95.1%.

[0026] Example 3 A method for preparing a methylbenzidine-based polyamide thin-layer composite nanofiltration membrane, comprising the following steps: (1) Soak the polyacrylonitrile ultrafiltration membrane in pure water for 4 h to remove the pore-retaining agent on the membrane surface; (2) Take out the above polyacrylonitrile ultrafiltration membrane, wipe the water droplets remaining on the surface of the ultrafiltration membrane with lint-free paper, and soak it in an ethanol aqueous solution with a methyl benzidine concentration of 0.1 wt% (ethanol ratio of 30 wt.%) for 5 min at 25°C. Take out the ultrafiltration membrane and remove the water droplets remaining on the membrane surface with a rubber roller for later use. (3) At 25°C, the polyacrylonitrile ultrafiltration membrane treated in step (2) was immersed in a hexane solution with a pyromellitic chloride concentration of 0.2 wt% and reacted for 5 min. (4) Place the filter membrane after the reaction in step (3) in an oven at 60 °C and heat for 8 min.

[0027] (5) The composite nanofiltration membrane obtained in step (4) is immersed in acetone for 12 h to obtain a methylbenzidine polyamide thin-layer composite nanofiltration membrane.

[0028] The separation performance test of the prepared composite nanofiltration membrane showed that the methanol flux was 30.3 LMH / bar and the rejection rate of Orange G (MW 452 Da) was 96.8%.

[0029] Example 4 A method for preparing a methylbenzidine-based polyamide thin-layer composite nanofiltration membrane, comprising the following steps: (1) Soak the polyacrylonitrile ultrafiltration membrane in pure water for 4 h to remove the pore-retaining agent on the membrane surface; (2) Take out the above polyacrylonitrile ultrafiltration membrane, wipe the water droplets remaining on the surface of the ultrafiltration membrane with lint-free paper, and soak it in an ethanol aqueous solution with a methyl benzidine concentration of 0.1 wt% (ethanol ratio of 30 wt.%) for 5 min at 25°C. Take out the ultrafiltration membrane and remove the water droplets remaining on the membrane surface with a rubber roller for later use. (3) At 25°C, the polyacrylonitrile ultrafiltration membrane treated in step (2) was immersed in a hexane solution with a concentration of 0.1 wt% of pyromellitic chloride and reacted for 10 min. (4) Place the filter membrane after the reaction in step (3) in an oven at 60 °C and heat for 8 min.

[0030] (5) The composite nanofiltration membrane obtained in step (4) is immersed in acetone for 12 h to obtain a methylbenzidine polyamide thin-layer composite nanofiltration membrane.

[0031] The separation performance test of the prepared composite nanofiltration membrane showed that the methanol flux was 33.4 LMH / bar and the rejection rate of Orange G (MW 452 Da) was 96.5%.

[0032] Example 5 A method for preparing a methylbenzidine-based polyamide thin-layer composite nanofiltration membrane, comprising the following steps: (1) Soak the polyacrylonitrile ultrafiltration membrane in pure water for 4 h to remove the pore-retaining agent on the membrane surface; (2) Take out the above polyacrylonitrile ultrafiltration membrane, wipe the water droplets remaining on the surface of the ultrafiltration membrane with lint-free paper, and soak it in an ethanol aqueous solution with a methyl benzidine concentration of 0.1 wt% (ethanol ratio of 30 wt.%) for 5 min at 25°C. Take out the ultrafiltration membrane and remove the water droplets remaining on the membrane surface with a rubber roller for later use. (3) At 25°C, the polyacrylonitrile ultrafiltration membrane treated in step (2) was immersed in a hexane solution with a pyromellitic chloride concentration of 0.3 wt% and reacted for 10 min. (4) Place the filter membrane after the reaction in step (3) in an oven at 60 °C and heat for 8 min.

[0033] (5) The composite nanofiltration membrane obtained in step (4) is immersed in acetone for 12 h to obtain a methylbenzidine polyamide thin-layer composite nanofiltration membrane.

[0034] The separation performance test of the prepared composite nanofiltration membrane showed that the methanol flux was 34.7 LMH / bar and the rejection rate of Orange G (MW 452 Da) was 96.1%.

[0035] Comparative Example 1 A method for preparing a composite nanofiltration membrane is as follows: (1) Soak the polyacrylonitrile ultrafiltration membrane in pure water for 4 h to remove the pore-retaining agent in the membrane; (2) Take out the above polyacrylonitrile ultrafiltration membrane, immerse it in an aqueous solution of ethanol with a concentration of 0.1 wt% m-phenylenediamine (the proportion of ethanol is 30 wt.%) at 25°C, take out the membrane after 5 min, and remove the water droplets remaining on the membrane surface with a rubber roller for later use; (3) At 25°C, the polyacrylonitrile ultrafiltration membrane treated in step (2) was immersed in a hexane solution with a pyromellitic chloride concentration of 0.2 wt% and reacted for 10 min. (4) Place the composite membrane after the reaction in step (3) in an oven at 60°C and heat for 8 min.

[0036] (5) The composite nanofiltration membrane obtained in step (4) is immersed in acetone for 12 h to obtain a thin-film composite nanofiltration membrane of m-phenylenediamine polyamide.

[0037] The separation performance test of the prepared composite nanofiltration membrane showed that the methanol flux was 3.56 LMH / bar and the rejection rate of the composite nanofiltration membrane for Orange G (MW 452 Da) was 98.1%.

[0038] Comparative Example 2 A method for preparing a composite nanofiltration membrane is as follows: (1) Soak the polyacrylonitrile ultrafiltration membrane in pure water for 4 h to remove the pore-retaining agent in the membrane; (2) Take out the above polyacrylonitrile ultrafiltration membrane, immerse it in an aqueous solution of 2,2'-biphenyldiamine with a concentration of 0.1 wt% ethanol (the proportion of ethanol is 30 wt.%) at 25°C, take out the membrane after 5 min, and remove the water droplets remaining on the membrane surface with a rubber roller for later use; (3) At 25°C, the polyacrylonitrile ultrafiltration membrane treated in step (2) was immersed in a hexane solution with a pyromellitic chloride concentration of 0.2 wt% and reacted for 10 min. (4) Place the composite membrane after the reaction in step (3) in an oven at 60°C and heat for 8 min.

[0039] (5) The composite nanofiltration membrane obtained in step (4) is immersed in acetone for 12 h to obtain a benzylamino polyamide thin-layer composite nanofiltration membrane, the surface morphology of which is as follows: Figure 5 As shown.

[0040] The prepared composite nanofiltration membrane was used to separate 4-p-nitroaniline (AR), Sudan Orange G (SOG), methyl orange (MO), orange yellow G (OG), acid fuchsin (AF), acid red 27 (AR27), and methylene blue (MB). The experimental results are as follows: Figure 6 As shown, the retention capacity gradually increases with the increase of dye molecular weight; the molecular weight cutoff of the above-mentioned polyamide thin-layer nanofiltration membrane is approximately 305 Da.

[0041] The prepared composite nanofiltration membrane was tested for permeation performance with various solvents, and the results are as follows: Figure 7 As shown, the composite nanofiltration membrane of this invention has a methanol permeation flux of 13.3 LMH / bar and an acetone permeation flux of 26.1 LMH / bar. Furthermore, the permeability of the composite nanofiltration membrane to various solvents exhibits a certain linear relationship with the binding parameters of the corresponding solvents.

[0042] Comparing Example 1 with Comparative Example 1, it can be seen that under the same conditions, when a non-planar twisted methylbenzidine monomer is used to replace the traditional planar m-phenylenediamine monomer, the methanol flux increases by nearly 7 times, while the rejection rate of Orange G (MW 452 Da) does not decrease significantly. Simultaneously, comparing with Comparative Example 2, it can be seen that compared with a similarly structured 2,2'-benzidine monomer, the methyl substituent, with its larger spatial volume, allows the molecule to be in a more twisted configuration. Therefore, after methylbenzidine replaces 2,2'-benzidine to prepare the composite nanofiltration membrane, its methanol flux increases by nearly 2 times, while its rejection rate of organic molecules does not decrease significantly, and the rejection rate of Orange G (MW 452 Da) remains above 97%. This fully demonstrates the significant performance advantages of our designed methylbenzidine molecule as an interfacial polymerization monomer for membrane fabrication.

[0043] Finally, it should be noted that the above examples are merely some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments and other modifications are possible. Any modifications, equivalent substitutions, or improvements made by those skilled in the art based on the disclosure of this invention should be considered within the scope of protection of this invention.

Claims

1. A method for preparing a methylbenzidine-based polyamide thin-film composite film, characterized in that, Includes the following steps: (1) Immerse the base membrane in deionized water for 6 h to fully remove the pore-retaining agent on the membrane surface. The base membrane is a polyacrylonitrile or polyimide ultrafiltration membrane. (2) Remove the soaked base film and drain the surface water. Then soak it in an aqueous solution of methyl benzidine compound alcohol at 25°C for 1-10 min. After soaking, remove the base film and remove the water droplets remaining on the surface of the base film for later use. (3) At 25°C, the base membrane treated in step (2) is immersed in an organic solution for 1-10 min and then removed and the organic phase solution on the surface of the membrane is removed with an organic solvent, wherein the organic phase solution contains polyacrylamide chloride; (4) Place the composite nanofiltration membrane after the reaction in step (3) in an oven at 40-70℃ and heat for 1-10 min to perform thermal crosslinking; (5) The composite nanofiltration membrane obtained in step (4) is immersed in an organic solvent for 1 h-20 h to obtain a methylbenzidine-based polyamide thin-layer composite membrane.

2. The method for preparing the methylbenzidine-based polyamide thin-film composite film as described in claim 1, characterized in that, The structure of the methylbenzidine compound in the aqueous alcoholic solution is shown below: 。 3. The method for preparing the methylbenzidine-based polyamide thin-film composite film as described in claim 1, characterized in that, The pore-retaining agent removed by pre-soaking in deionized water is one or a mixture of glycerol and polyethylene glycol.

4. The method for preparing the methylbenzidine-based polyamide thin-film composite film as described in claim 1, characterized in that, The concentration of the aqueous solution of the methylbenzidine compound is 0.1 wt%-2 wt%.

5. The method for preparing the methylbenzidine-based polyamide thin-film composite film as described in claim 1, characterized in that, The solvent for the aqueous solution of the methylbenzidine compound in step (2) is a mixture of alcohol and water, and the alcohol is at least one of ethanol, methanol, and isopropanol.

6. The method for preparing the methylbenzidine-based polyamide thin-film composite film as described in claim 5, characterized in that, The alcohol content in the solvent of the aqueous solution of the methyl benzidine compound in step (2) is 0.1%-100 wt%.

7. The method for preparing the methylbenzidine-based polyamide thin-film composite film as described in claim 1, characterized in that, The polyacryl chloride in step (3) is one or a mixture of several of pyromellitic chloride, isophthaloyl chloride, and terephthaloyl chloride; the concentration of the polyacryl chloride is 0.1 wt%-0.3 wt%.

8. The method for preparing the methylbenzidine-based compound polyamide thin-film composite film as described in claim 1, characterized in that, The organic solution in step (3) is prepared by dissolving polyacrylamide chloride in an organic solvent, wherein the organic solvent is at least one of n-hexane, isoalkanes or cyclohexane.

9. The method for preparing the methylbenzidine-based polyamide thin-film composite film as described in claim 1, characterized in that, The organic solvent in step (5) is at least one of acetone, tetrahydrofuran, or ethanol.